Excited-state dynamics of dipyrrolyldiketone difluoroboron complexes. Issue 3 (4th January 2022) - Sato, Ryota; Okajima, Hajime; Sugiura, Shinya; Haketa, Yohei; Kinoshita, Yusuke; Tamiaki, Hitoshi; Sakamoto, Akira; Maeda, Hiromitsu; Kobayashi, Yoichi
Abstract : Excited-state dynamics of a π-conjugated anion receptor was revealed in detail by time-resolved visible and infrared spectroscopies combined with quantum chemical calculations. Abstract : Anion-responsive photofunctional materials have been extensively studied because anions are important for biotic activity and constitute the building blocks of elegant supramolecular architectures. A number of fluorescent anion receptors that can probe anions in their environments have been reported, but the excited states of many of these molecules remain elusive. Studies on excited-state dynamics provide fruitful information for optimizing the emission properties, minimizing the photodegradation and photorelease of anions, and exploring novel photofunctions. In this study, we investigated the excited-state dynamics of an aryl-substituted dipyrrolyldiketone difluoroboron complex, a π-conjugated anion receptor, by time-resolved visible and infrared absorption spectroscopy and emission decay measurements combined with quantum chemical calculations. Anion binding was found to alter the radiative and nonradiative rate constants and the excited-state absorption of the anion receptor. In contrast, the molecular structures and binding abilities were similar in the S0 and S1 states.